COSMOCHEMICAL CONSTRAINTS ON THE SULFUR CONTENT IN THE EARTHS CORE - Dreibus G.; Palme H. (My University, 1996)
The density of the Earth's core (32.5% of the mass of the Earth) is about 8% less than that of pure metallic Fe under similar P, T conditions, requiring the presence of a substantial amount of a light element or light elements in the core (McQueen and Marsh, 1960, 1966). Sulfur is a good candidate for reducing the density. On the basis of shock wave experiments, Ahrens (1979) estimated that 9-12% S in the core would be sufficient to account for the observed density difference. This corresponds to a S-content of 2.9-3.9% for the bulk Earth.Here we present an estimate of the bulk Earth S-content which is based on the volatility of S in the solar nebula and the general depletion of volatile elements in meteorites and in the Earth. It is suggested that the CI-normalized S-abundance of the bulk Earth is similar to, or even lower than, the CI-normalized abundance of Zn, an element of similar volatility as S in the reducing environment of the solar nebula. Since the Zn content of the mantle of the Earth is well known and since the core is most likely free of Zn, the bulk Earth S-content can be calculated from the Zn-abundance of the mantle. A maximum bulk Earth S-content of 0.56% and a corresponding maximum S-content of the core of 1.7% are estimated. The S-content of the mantle is so low that the contribution to the bulk Earth S-content is negligible. The upper limit of S in the core as derived from cosmochemical constraints is much too low to produce the required decrease in the core's density. At least one other light element is needed.